Comparabilidade contábil e o custo de capital próprio: uma análise no mercado de capitais brasileiro - Silva Filho, Augusto Cezar da Cunha e (2020)
This thesis investigates the influence of accounting comparability on the cost of equity of Brazilian companies. The literature points out that greater accounting comparability results in more accurate assessments of the individual performance of companies, since it reduces the cost of collecting and analyzing information between a given company over a period and, also, between peer companies. In addition, comparable information helps investors to identify and understand economic similarities and differences between firms and thus make more efficient investment decisions. Given this context, investors are likely to demand lower expected returns when faced with more comparable accounting information, resulting in a lower cost of equity. For the execution of this study, a sample was used based on data from the companies listed in Brasil, Bolsa, Balcão (B3), in the period from 2001 to 2018. To measure accounting comparability, the accounting function similarity model developed by DeFranco, Kothari and Verdi (2011) was used as the main metric, and to measure the implicit cost of equity, the Easton model (2004) was used. The results showed that the level of accounting comparability between companies in the same sector increased after the adoption of International Financial Reporting Standards (IFRS). There was a negative and statistically significant relationship between the cost of equity and accounting comparability between companies in the same sector. In addition, this relationship is more pronounced for companies located in more competitive sectors, indicating that market competitiveness acts as an effective external governance mechanism (market competitiveness was calculated using the Herfindahl index). In general, the results of this thesis suggest that accounting comparability plays an important role in reducing investment risks, contributing to the efficient allocation of investors’ capital. Finally, this work contributes to the national and international literature by demonstrating the economic benefits of accounting comparability.